PENDAMPINGAN WIRAUSAHAWAN MENUJU UMKM BANGKIT KEMBALI PASCA PANDEMI DI YOGYAKARTA - Jana, Padrul; Danuri, Danuri; Indriati, Inayat Hanum; Asriyanti, Isma (Jurnal Abdi Masyarakat, 2023)
The Covid-19 pandemic has not only had an impact on health problems, but has penetrated the economic and business sectors. One of those affected by this outbreak is UKM "Dermayu Catering Jogja". This condition caused problems including (1) Orders decreased because events involving crowds of residents were prohibited and employees were unable to pay. (2) Not yet optimal marketing by utilizing information technology, managerial production processes that have not been stable after the vacuum due to Covid-19, have not been able to keep production and sales bookkeeping. The solutions offered are through mentoring and training on market mapping and targeting, production and marketing managerial, financial accounting, as well as digitalization and standardization of product quality. Through mentoring and training for partners, the realization of Entrepreneurs is formed in the UKM "Dermayu Catering Jogja" which has risen, is able to compete, and produces better products than before. Entrepreneurs rise and recover more quickly after the pandemic situation that hit Indonesia. This can be seen in post-training, mentoring and monitoring of Dermayu catering Yogyakarta, acceptance of catering orders has increased. Another indicator of the increase in the number of turnover of catering orders, partners have opened kiosk outlets displaying products produced by Dermayu Catering.   Keywords : Catering, Pandemic, SMEs, Rising Entrepreneurs.